Synthesis of fluorescent 3-benzoxazol-2-yl-coumarins - X. H. Luan (2002)
Twelve 3-benzoxazol-2-yl-coumarins (1-3) were synthesised by reacting various ortho-aminophenols with three coumarin-3-carboxylic acids either directly or by formation of the intermediate amide. The cyclodehydrating agent was polyphosphoric acid (PPA). The compounds were characterised by spectroscopic methods. Absorption and fluorescence spectra of the compounds have also been recorded.